2023
DOI: 10.1093/jac/dkad276
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of linezolid in bone and joint infections: a retrospective analysis of adverse effects

Karin Veerman,
Jon Goosen,
Karin Spijkers
et al.

Abstract: Objectives Antibiotic treatment for bone and joint infections generally lasts for 6 weeks or longer. Linezolid may be a good option for treating bone and joint infections, but there is an increased risk of potential serious adverse drug events (ADEs) when used for more than 28 days. The aim of this study was to obtain detailed information on the type and time to occurrence of the patient-reported ADEs, the dynamics of haematopoiesis over time, and the reasons for early discontinuation of line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Most importantly, we provide a comprehensive study of the specific time of onset following linezolid administration in each organ system. Previous researchers have reported the median time to occurrence of some specific ADEs for linezolid dosing (Matsumoto et al, 2014;Jaspard et al, 2020;Veerman et al, 2023). Although these results may not reflect the actual TTO given the population in the clinical trial, our results are close to the findings and provide a more detailed and concrete list.…”
Section: Tto Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Most importantly, we provide a comprehensive study of the specific time of onset following linezolid administration in each organ system. Previous researchers have reported the median time to occurrence of some specific ADEs for linezolid dosing (Matsumoto et al, 2014;Jaspard et al, 2020;Veerman et al, 2023). Although these results may not reflect the actual TTO given the population in the clinical trial, our results are close to the findings and provide a more detailed and concrete list.…”
Section: Tto Analysissupporting
confidence: 80%
“…Gastrointestinal-related symptoms (nausea, vomiting, and diarrhea) were the most common reasons for discontinuation of the drug (Moise et al, 2002;Noel et al, 2012). Nausea (Shorr et al, 2015), gastrointestinal intolerance (Veerman et al, 2023), diarrhea, and vomiting (Shi et al, 2023) were the most common side effects reported in previous studies. A single-center retrospective observational study (Tsutsumi et al, 2022) found that female gender is an independent risk factor for linezolid-induced vomiting, which may be associated with multiple signaling pathways including D2, 5-HT3, and neurokinin-1 receptors (Navari and Aapro, 2016).…”
Section: Gender-based Differencesmentioning
confidence: 86%
“…For patients allergic to penicillin, intravenous high-dose vancomycin or daptomycin are alternatives. The only oral alternative is linezolid, yet its toxicity profile may constrain its long-term usage [ 145 ].…”
Section: Antibiotic Therapymentioning
confidence: 99%